Peroxynitrite does not decompose to singlet oxygen ((1)Δ(g)O(2)) and nitroxyl (NO(−)) - Martinez, Glaucia R. (The National Academy of Sciences, 2000)
According to Khan et al. [Khan, A. U., Kovacic, D., Kolbanovskiy, A., Desai, M., Frenkel, K. & Geacintov, N. E. (2000) Proc. Natl. Acad. Sci. USA 97, 2984–2989], peroxynitrite (ONOO(−)) decomposes after protonation to singlet oxygen ((1)Δ(g)O(2)) and singlet oxonitrate (nitroxyl, (1)NO(−)) in high yield. They claimed to have observed nitrosyl hemoglobin from the reaction of NO(−) with methemoglobin; however, contamination with hydrogen peroxide gave rise to ferryl hemoglobin, the spectrum of which was mistakenly assigned to nitrosyl hemoglobin. We have carried out UV–visible and EPR experiments with methemoglobin and hydrogen peroxide-free peroxynitrite and find that no NO(−) is formed. With this peroxynitrite preparation, no light emission from singlet oxygen at 1270 nm is observed, nor is singlet oxygen chemically trapped; however, singlet oxygen was trapped when hydrogen peroxide was also present, as previously described [Di Mascio, P., Bechara, E. J. H., Medeiros, M. H. G., Briviba, K. & Sies, H. (1994) FEBS Lett. 355, 287–289]. Quantum mechanical and thermodynamic calculations show that formation of the postulated intermediate, a cyclic form of peroxynitrous acid (trioxazetidine), and the products (1)NO(−) and (1)Δ(g)O(2) requires Gibbs energies of ca. +415 kJ⋅mol(−1) and ca. +180 kJ⋅mol(−1), respectively. Our results show that the results of Khan et al. are best explained by interference from contaminating hydrogen peroxide left from the synthesis of peroxynitrite.